Función conjunta de la investigación y la extensión en el progreso agrícola - Hopp, Henry (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Technical service organizations for farmers generally provide for two kinds of efforts: research to discover facts and principles that will solve production problems, and education or extension to aid farmers in putting the solutions into effect. As technical service organizations grow, they tend to divide into separate organizational units for each of these activities. However, agricultural development cannot take place ef-fectively as separate and unrelated efforts. After solutions are worked out at the research-station level, varying degrees of intermediate adaptation are generally required before a practice is ready for application by farmers. Such effort requires cooperative participation of research and extension specialists Problems of applicability can be grouped under five main headings: regionality, practicability, profitableness, variability, and compara-bility Until problems of applicability are adequately answered, practical recommendations from research are haphazard and unreliable. The cooperative nature of the work requires an organizational procedure that will determine the type of testing required for specific problems and will assure definite assignment of responsibility in carrying out the testing and in reaching practical recommendations in their regional aspects. A joint technical agricultural commission in which research and extension would be represented is outlined as an example of a form of organizational procedure for testing applicability.